Analysis of The Antioxidant Potential of Ethanol Extracts from Pacing Plant (Costus speciosus) With DPPH Method - Riany, Hesti; Wahyuningtyas, Regita Kusuma (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2024)
Antioxidants are reducing compounds utilized to protect the body from oxidative degradation. One of the plants, Costus speciosus, commonly known as pacing, is believed to have potential as a natural source of antioxidants. The aim of this research is to determine the antioxidant content and secondary metabolite compounds present in the ethanol extracts of pacing stems, leaves, and flowers. Antioxidant measurements were conducted using the 1,1-diphenyl-2-picrylhydrazine (DPPH) method. The antioxidant content was analyzed using probit analysis and calculating the IC50 value. The content of secondary metabolite compounds was analyzed using thin-layer chromatography (TLC) tests. The research results indicate that the ethanol extracts of pacing stems, leaves, and flowers contain antioxidants. The highest antioxidant content was found in the leaves with an IC50 value of 17.8 ppm, followed by the stems with an IC50 value of 24.22 ppm, and the flowers with an IC50 value of 24.85 ppm. The secondary metabolite content in pacing plants showed the presence of flavonoids and alkaloids in the leaves, flavonoids and phenols in the stems, while only flavonoids were detected in the flowers.AbstrakAntioksidan adalah senyawa pereduksi yang digunakan untuk melindungi tubuh dari degradasi oksidatif. Salah satu tanaman yaitu Costus speciosus atau yang biasa dikenal dengan nama pacing diyakini memiliki potensi sebagai sumber antioksidan alami. Penelitian ini bertujuan untuk mengetahui kandungan antioksidan dan senyawa metabolit sekunder yang terdapat pada ekstrak etanol batang, daun, dan bunga pacing. Pengukuran antioksidan dilakukan dengan menggunakan metode 1,1-difenil-2-pikrilhidrazil (DPPH). Kandungan antioksidan dianalisis dengan menggunakan analisis probit dan menghitung nilai IC50. Kandungan senyawa metabolit sekunder dianalisis menggunakan uji kromatografi lapis tipis (KLT). Hasil penelitian menunjukkan bahwa ekstrak etanol batang, daun, dan bunga pacing mengandung antioksidan. Kandungan antioksidan tertinggi terdapat pada bagian daun dengan nilai IC50 sebesar 17,8 ppm, diikuti oleh bagian batang dengan nilai IC50 sebesar 24,22 ppm, dan bagian bunga dengan nilai IC50 sebesar 24,85 ppm. Kandungan metabolit sekunder pada tanaman mondar-mandir menunjukkan adanya flavonoid dan alkaloid pada daun, flavonoid dan fenol pada batang, sedangkan pada bunga hanya terdeteksi adanya flavonoid